2016
DOI: 10.1080/13816810.2016.1214971
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological approaches to restoring lens transparency: Real world applications

Abstract: Cataract is the most common cause of blindness and a major cause of visual impairment worldwide. As the world's population ages, cataract-induced visual impairment is of increasing prevalence, and treatment is limited to those with access to surgical care. While cataracts are mainly a disease of the elderly, infantile cataracts lead to lifelong visual impairment if untreated. Even in those with surgical treatment early in life, visual prognosis is often guarded. Consequently, there is an increasing impetus for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Cataracts are the leading cause of legal blindness worldwide. Until now, there has not been an effective pharmacological agent that can inhibit or reverse the progression of cataracts, and the search for affordable and nonsurgical pharmacological treatment is necessary to delay the progression of lens opacification [ 17 , 18 ]. The effects of ghrelin on HLECs and the regulatory mechanism of those effects have never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Cataracts are the leading cause of legal blindness worldwide. Until now, there has not been an effective pharmacological agent that can inhibit or reverse the progression of cataracts, and the search for affordable and nonsurgical pharmacological treatment is necessary to delay the progression of lens opacification [ 17 , 18 ]. The effects of ghrelin on HLECs and the regulatory mechanism of those effects have never been reported.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 5 , 7 , 38 , 39 , 40 Although in the past few decades, ARC can be effectively treated by surgery, it is still the most common cause of blindness in the world, and there is still no affordable effective drug that can inhibit or reverse the progress of cataract. 41 In view of the fact that oxidative stress plays an important role in the pathogenesis of cataract, reducing and preventing oxidative stress has become a reasonable potential therapeutic target for cataract, 39 while for senile cataracts, which account for the majority of cataract, there may be long-term low-and medium-dose UVB exposure, and autophagy flux decreases with age. This aggravates the progression of cataract, and the use of autophagy inducers may help to restore autophagy flux and reduce oxidative damage in HLECs to prevent and improve cataract progression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the rapid development of cataract surgery technology over the years, surgery remains a challenge due to its cost and the increasing number of patients, especially in developing countries. Pharmacologic therapy may therefore be an efficient method to reduce the disease burden and medical costs and to benefit patients in rural areas (9). Over the last few decades, numerous Figure 1 A novel high-throughput drug-screening platform for anti-cataract drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological therapy is therefore an ideal choice for cataracts prevention and treatment, which also has both a lower economic burden and higher availability. Drug screening research for cataracts has attracted a lot of attention, and some recent studies have reported several compounds that could prevent and dissolve protein aggregates in the lens, offering a novel anti-cataract drug screening strategy (8,9). In this article, we will review the development and application of anti-cataract drugs based on their various targets (Table 1).…”
Section: Introductionmentioning
confidence: 99%